ANALISIS PREFERENSI KONSUMEN TERHADAP SITUS PERMAINAN ONLINE - , Hans Yulianto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objective of this study to analyze the influence of website quality, service on website, website design and security to use website, influence of website trust to play a game intention and moderation effect of game playing pattern on relationship between website trust and play a game intention. On this research, total samples are 100 respondents that live in Yogyakarta area at time this research done and they ever use game online. This research location site on three areas on Sleman that has many game online facilities, such as Jl Kaliurang KM 5, Jl. Kaliurang KM 9 and Jl Gejayan. This research prove about the influence of website quality, service on website, website design and security to use website. The website trust has an effect to play a game intention. Besides that, this research prove about moderation effect of game playing pattern on relationship between website trust and play a game intention.